Roadmap on structured light. (25th November 2016) - Rubinsztein-Dunlop, Halina; Forbes, Andrew; Berry, M V; Dennis, M R; Andrews, David L; Mansuripur, Masud; Denz, Cornelia; Alpmann, Christina; Banzer, Peter; Bauer, Thomas; Karimi, Ebrahim; Marrucci, Lorenzo; et al.
Abstract: Structured light refers to the generation and application of custom light fields. As the tools and technology to create and detect structured light have evolved, steadily the applications have begun to emerge. This roadmap touches on the key fields within structured light from the perspective of experts in those areas, providing insight into the current state and the challenges their respective fields face. Collectively the roadmap outlines the venerable nature of structured light research and the exciting prospects for the future that are yet to be realized.